Market insertion of 4.0 technologies in poultry farming - Dos Santos Pereira, Vivian; Maria Santana de Melo, Yasmin; Christino de Oliveira Soares, Caio; Jennyfer Santos de Araújo, Steffany; Gabrielly Silva Souza, Nathalia; Raffaela Dantas de Freitas, Pâmella; Virginia de Carvalho, Zulmara (Seven Editora, 2023)
The poultry industry has expanded with the insertion of enabling technologies. Being included in the consumer market, its economic role is of great importance. In view of the growing market and its contribution to the economy, the analysis of market technology was made, from the level of insertion in the economic techno paradigm 4.0. Through market prospection it was possible to obtain the result of the integration of industry 4.0 in the poultry sector within a culture of innovation. DOI: https://doi.org/10.56238/tfisdwv1-153